Empirical Analysis of the Effect of Corporate Social Responsibility on Host Community Development among Selected Manufacturing Firms in Southwest Nigeria - Alo, Ebenezer Adebisi; Adeyokun, Mercy (NIU Journal of Social Sciences, 2022)
For enterprises to be socially accountable to their host communities and stakeholders there is a self-regulatory paradigm known as corporate social responsibility (CSR). The study examined the effect of corporate social responsibility on the development of host community of selected manufacturing firms in South West, Nigeria. The study employed a descriptive research design and the data for the study were collected through the administration of a well-structured questionnaire. The population of the study consisted of 515 employees of International Brewery Plc Ilesa of which 183 were senior and management staff; Nigeria Brewery plc Ibadan with a total population of 490, of which 165 were senior and management staff and Guinness Nigeria Plc with a total population of 580, of which 210 were senior and management staff. Stratified sampling technique was used to arrive at the sample size for the study. The Taro Yamane (1973) formula was use to arrive at a sample size of 304. A total of 304 copies of the questionnaire were administered on the respondents, out of which 255 were retrieved and analysed. Regression and Correlation Analyses were employed in analyzing the data collected. Findings of the study revealed a positive relationship between corporate social responsibility and development of host community. Furthermore, the R 2 value = (0.237), implied that philanthropic activities have statistical significant effect on the development of host communities in South West, Nigeria and a statistically significant correlation existed between economic activities and development of host community at 95% confident limit and sig 0.000. The study concluded that corporate organizations that engage in philanthropic activities such as corporate social responsibility enjoy a sense of satisfaction and/or fulfillment by benefiting other people and developing the host community. The study recommended that corporate entities should adopt the practice of corporate social responsibility by developing their host communities, employing people, creating jobs and advancing skill development. Keywords: Corporate Social Responsibility, Development, Host Community, Philanthropic, Economic.